PENGUATAN NILAI KEAGAMAAN BAGI KELOMPOK PENGAJIAN REMAJA DI KELURAHAN TANAH SIRAH PIAI NAN XX - Iswadi Iswadi (IAIN Batusangkar, 2019)
The potential of religion that has existed when humans are born if not treated properly, then that potential will experience fade or disappear altogether, so people in their lives assume that religion is not important in their lives. This study discusses the strengthening of the model of religious guidance for adolescents through wirid activities in Tanah Sirah Piai Nan XX Lubuk Begalung. This study uses a qualitative descriptive approach where researchers describe the overall model of adolescent coaching on intellectual, spiritual and social aspects as well as ideas related to strengthening the coaching model by forming an organization, increasing activities by carrying out dawn in congregation, Maghrib reciting and giving rewards.